(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
The domus of Piazza Marconi was built in the Augustan age in the southern end of the Roman city. In the I century, the domus was the home of a family of great economic possibilities, certainly important within the social and politic structure of the old Cremona; it is revealed by the high quality of the frescoes, the floors, the mosaics, and the stone furnishings that adorned the courtyards and reception rooms. Although it is likely that the majority of bronze objects have been stolen by soldiers during the sack of Vespasian in 69 AD, the remaining findings, including containers and furniture, offer an interesting picture of the metal furnishings in a rich home of the Cisalpine, with a terminus ante quem that immediately recalls the more famous model of the Vesuvian cities.